x+6+x+9+x+3=x

Simple and best practice solution for x+6+x+9+x+3=x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x+6+x+9+x+3=x equation:


Simplifying
x + 6 + x + 9 + x + 3 = x

Reorder the terms:
6 + 9 + 3 + x + x + x = x

Combine like terms: 6 + 9 = 15
15 + 3 + x + x + x = x

Combine like terms: 15 + 3 = 18
18 + x + x + x = x

Combine like terms: x + x = 2x
18 + 2x + x = x

Combine like terms: 2x + x = 3x
18 + 3x = x

Solving
18 + 3x = x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1x' to each side of the equation.
18 + 3x + -1x = x + -1x

Combine like terms: 3x + -1x = 2x
18 + 2x = x + -1x

Combine like terms: x + -1x = 0
18 + 2x = 0

Add '-18' to each side of the equation.
18 + -18 + 2x = 0 + -18

Combine like terms: 18 + -18 = 0
0 + 2x = 0 + -18
2x = 0 + -18

Combine like terms: 0 + -18 = -18
2x = -18

Divide each side by '2'.
x = -9

Simplifying
x = -9

See similar equations:

| 8a-5a-3a+a=20 | | 1=2(5-6x) | | 10v=2(9-2v) | | 11=m+20 | | 3ky-12kz+24kw=0 | | q(q+7)=0 | | 1-4p=-2(5p-1)+5 | | 2x+3y-2=5 | | -15=b-16 | | (2c-9)(c-1)=0 | | 31.25/25= | | 16x^2-36=-72 | | 2(x-7)+5=-9 | | 6s^4t^3-12s^3t^4=0 | | n(n-9)=0 | | 6x+7yx+9y=0 | | y^2+y-112=0 | | j(j-8)=0 | | 25/31.25= | | -9m=18 | | 4m(m-8)=0 | | 6=-4y+18 | | b^5+10b^4=0 | | 1/4x-2/5=5/6 | | (w-8)(3w+7)=0 | | 4-(2x+3)=5x-8 | | 1=v-8 | | -5-4r=-(1-2r) | | -9=2+p | | 8x-(5-x)+2(3x-4)=2 | | 3x^2=-18 | | 3r-4=5(r-1) |

Equations solver categories